PENAMBAHAN BERBAGAI ARAS ”STARTER FUNGSIONAL” DALAM FERMENTASI LIMBAH PABRIK PAKAN TERHADAP NILAI POTENSIAL HIDROGEN (pH) DAN TOTAL BAKTERI ASAM LAKTAT (BAL) - E.D.K. Marhaen; Cahya Setya Utama; B.I.M. Tampoebolon (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
The experiment was aimed to examine the levels that can produce the best starter lactic acid bacteria (LAB)by a potential value of hydrogen ( pH ) acid. The materials were cabbage, mustard, molasses, salt, pollard, functional starter, distilled water, feed mill waste, plastic, electric scales, grand moisture tester, oven, thermometer, drying cabinets, pH meter, measuring cup, beaker glass and trays. The experiment used a completely randomized design (CRD) is 4 treatments with 4 replications.The experiment were used 0, 1, 2 and 3 % starter levels. The parameters werethe potential value of Hydrogen (pH) and total lactic acid bacteria (LAB). The result was showed thatthere was pH decrease of the fermented feed by using functional starter although not significant. The pH decrease caused by lactic acid of production microorganisms, including lactic acid bacteria and Saccharomyces cereviceae in extract vegetable waste fermentation (ELSF) and gram positive bacteria. Based on laboratory analysis did not find any lactic acid bacteria but found a Saccharomyces cereviceae and gram positive bacteriawhich produceed the lactic acid. This was due to the drying process is too long with the high temperatures resulting in BAL could not live, while Saccharomycescereviceae alive because it was more tolerant to high temperatures.